Surface-doped layered battery positive electrode material as well as preparation method and application thereof

By constructing a lattice-matched layered in situ reconstruction layer on the surface of the positive electrode material of the sodium ion battery, the problems of short cycle life and poor air stability of the layered transition metal oxide material in the sodium ion battery are solved, and the effect of significantly improving the cycle stability and air stability is achieved.

CN119890292AActive Publication Date: 2025-04-25PEKING UNIV

Patent Information

Application Number
CN202510061469.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The positive electrode materials of sodium ion batteries, especially layered transition metal oxides, face complex phase transition behaviors, high sensitivity to water and oxygen, and interface side reactions, resulting in a short cycle life of the battery and a fast capacity decay, limiting its commercialization process.

Method used

By constructing a lattice-matched surface layer in situ reconstruction layer on the surface of the layered material, ion exchange and surface reconstruction are achieved using metal salts in the aprotic solvent and auxiliary complexing agent to form a uniform Na1-xIyTMO2 gradient symbiotic layer to inhibit lattice oxygen precipitation and interface side reactions.

Benefits of technology

It significantly improves circulation stability and air stability, extends the cycle life of the battery, and improves ion mobility and rate performance while maintaining high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890292A_ABST
    Figure CN119890292A_ABST
Patent Text Reader

Abstract

The invention relates to a surface-doped layered battery positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of sodium-ion battery materials. According to the method, a surface layered in-situ reconstruction layer with matched crystal lattices is constructed in an aprotic solvent under the assistance of a complexing agent, so that the surface modification of the positive electrode material is realized. The preparation method comprises the following specific steps: firstly, preparing a layered sodium ion oxide Na < 1-x > TMO2 through solid-phase sintering, sol-gel or a coprecipitation method; then placing the positive electrode material in an aprotic solvent solution containing a metal salt, and carrying out surface ion exchange and reconstruction through microwave, heating, stirring or ultrasonic treatment and the like; and finally, filtering, washing and annealing the reacted mixture. The cycling stability, the ion mobility and the air stability of the material are remarkably improved through surface doping, the irreversible reaction and the interface side reaction of lattice oxygen are effectively inhibited, and meanwhile the high energy density of the material is kept. The method has the advantages of simple process, low cost and easiness in large-scale production, and is suitable for surface modification of the sodium-ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion and lithium ion batteries, and in particular to a surface-doped layered battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have become a research hotspot in the field of energy storage in recent years due to their abundant resources, low cost and high safety. As the global energy structure transforms towards sustainable development, the application potential of sodium-ion batteries in large-scale energy storage, low-speed electric vehicles, communication base stations and other fields has become increasingly prominent. However, the cathode materials of sodium-ion batteries, especially layered transition metal oxides (Na x TMO 2 ), there are still many challenges in practical applications, including complex phase change behavior, high sensitivity to water and oxygen, and interfacial side reactions. These problems directly lead to short battery cycle life and rapid capacity decay, which seriously restricts its commercialization process.

[0003] Layered oxide cathode materials (Na x TMO 2 ) has attracted much attention due to its high specific capacity and energy density. According to the oxygen coordination environment of sodium ions, Na x TMO 2 It is mainly divided into O3 phase (octahedral coordination) and P2 phase (triangular prism coordination). The O3 phase material has a higher initial sodium content and can release more sodium ions, but its structure is compact and the sodium ion migration rate is low; the P2 phase material has a larger sodium interlayer spacing, which is conducive to the rapid transmission of sodium ions, but its initial sodium content is low and its capacity is limited. Although these materials show excellent performance in theory, in practical applications, problems such as irreversible lattice oxygen precipitation, phase change and interfacial side reactions under high voltage seriously affect their electrochemical performance. In addition, the high sensitivity of layered oxide positive electrode materials to water and oxygen also increases the difficulty of their preparation and storage. When exposed to air, the surface of the material easily reacts with water and carbon dioxide to produce by-products such as sodium carbonate, which further deteriorates its electrochemical performance.

[0004] In order to improve the performance of layered oxide positive electrode materials, the existing technology mainly adopts modification methods such as doping or coating. For example, by doping different metal ions (such as alkali metals, alkaline earth metals or rare earth elements) to stabilize the crystal structure, or by coating a protective layer to reduce interface side reactions. However, these methods still have limitations: doping modification may lead to the replacement of some electrochemically active ions, thereby reducing the overall capacity of the material; coating modification is difficult to control the uniformity of the coating layer, and it is easy to cause structural damage to water-sensitive materials and reduce cycle performance. Therefore, there is an urgent need for a modification method that can effectively inhibit lattice oxygen precipitation and improve interface stability while maintaining high material capacity, so as to promote the widespread application of sodium ion batteries.

[0005] The present invention is proposed based on the above background, and aims to construct a lattice-matched surface layered in-situ reconstruction layer through a surface doping modification method, thereby protecting the bulk material during the charge and discharge process, inhibiting lattice oxygen redox and interface side reactions, and improving cycle stability and air stability. Summary of the invention

[0006] The purpose of the present invention is to provide a surface-doped layered battery positive electrode material and a preparation method and application thereof, wherein a lattice-matched surface layered in-situ reconstruction layer is constructed with the aid of a complexing agent of the layered material in a non-protonic solvent, so as to protect the bulk material during the charge and discharge process, inhibit lattice oxygen redox and interface side reactions, and improve cycle stability and air stability.

[0007] The technical solution of the present invention is as follows:

[0008] A surface doped layered battery positive electrode material, the general structural formula of which is: Na 1-x I y TMO 2 , where 0≤x<1, 0≤y<1. I is one or more of alkali metals, alkaline earth metals, transition metals, and rare earth metals such as Li, Ca, Sr, Ba, Zn, K, La~Lu; TM is one or more of metal elements such as Ni, Co, Mn, Fe, Cu, Al, Mg, and Cr.

[0009] The method for preparing the surface-doped layered battery positive electrode material comprises the following steps:

[0010] S01: Well-crystalline layered sodium ion oxide Na using solid phase sintering, sol-gel, coprecipitation or commercial purchase 1-x TMO 2 (x≥0), wherein TM is one or more of Ni, Fe, Mn, Co, Cu, Ti, Li, Al, Mg, Cr, and its configuration is O3 phase or P2 phase.

[0011] S02: The positive electrode material Na 1-x TMO 2 Place in metal salt (I n+) and an auxiliary complexing agent in a non-protonic solvent solution, the solvent is acetone, dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide; the metal salt is a sulfate, halide, nitrate, phosphate or complex salt that can be dissolved in an organic solvent; the doping ion is an alkali metal, alkaline earth metal or rare earth element; the auxiliary complexing agent is a small molecule or polymer such as phytic acid, dopamine, tannic acid, polyvinylpyrrolidone, etc. The target ions are involved in the surface of the layered material by microwaves, heating, stirring, ultrasound, etc. to achieve ion exchange and surface reconstruction. The reaction process is controlled by controlling the concentration, time, temperature, mechanical strength, etc. of the reaction to achieve uniform distribution of the target ions on the surface of the positive electrode particles.

[0012] S03: Filter, wash and anneal the reaction mixture. The solvent used for washing can be the solvent used to dissolve metal salts during ion exchange, in order to remove metal ions that have not reacted fully and anions adsorbed on the surface. Whether additional sodium source is needed depends on the selected positive electrode material. The annealing temperature ranges from 400 to 1000°C, the annealing time is 0.5 to 10 hours, and the annealing atmosphere is selected from air, argon or oxygen atmosphere.

[0013] Based on the common characteristics of layered positive electrode materials for sodium ion batteries, the present invention proposes a method for modifying layered positive electrode materials by surface ion reaction with a high sensitivity to water and oxygen, which maintains capacity and is simple and efficient. The method can be directly modified on the finished positive electrode material, alleviate the surface side reaction between the material and the electrolyte, inhibit lattice oxygen precipitation, improve water and oxygen stability, extend the cycle life, and achieve the improvement of the electrochemical performance of the material.

[0014] Another object of the present invention is to provide an application of a surface-doped layered battery positive electrode material in a sodium ion battery.

[0015] The beneficial effects of the present invention are:

[0016] 1. Significantly improved cycle stability: Solvent-assisted I n+ Surface reconstruction, part I n+ Enter the surface of the positive electrode particles and build a uniform layer of Na 1-x I y TMO 2 The gradient symbiotic layer significantly improves the structural stability, inhibits the irreversible reaction of lattice oxygen, and improves the cycle stability.

[0017] 2. Improve ion mobility and rate performance: Since the addition of I enhances the interlayer force of layered oxides, I with a larger radius is selected. n+ This will cause local lattice changes, thereby improving ion mobility and rate performance.

[0018] 3. Improve air stability: The enrichment of I on the surface reduces the erosion of air on the O3-type sodium positive electrode, thereby further improving air stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : Scanning electron microscope image (SEM) of the surface modified material, scale bar is 1 μm. The image shows that the surface of the modified material is smooth and dense, without obvious impurities or defects, indicating that the surface modification process does not damage the material morphology, and the modified layer evenly covers the particle surface.

[0020] Figure 2 :X-ray diffraction pattern (XRD) of the surface modified material. The diffraction pattern shows that the modified material has good crystallinity, the diffraction peaks completely match the standard spectrum of the O3 phase layered structure, and no other impurities are detected, proving that the modification process does not introduce additional impurities or change the crystal structure of the material.

[0021] Figure 3 :Scanning electron microscope (STEM) image and energy dispersive X-ray spectroscopy (EDS) element distribution map of the surface of the modified positive electrode particles, the scale is 100nm. The STEM image clearly shows the microstructure of the particle surface, and the EDS spectrum shows that the transition metal elements (such as Ni, Fe, and Mn) are evenly distributed inside the particles, while the target ions (such as rare earth elements) show a significant enrichment effect at the edge of the particles, indicating that the surface reconstruction layer is successfully constructed.

[0022] Figure 4 : Comparison of half-cell cycle performance of O3 cathode materials at 1C rate before and after rare earth metal surface modification. The results show that the cycle stability of the modified battery is significantly improved, and the capacity retention rate is significantly higher than that of the unmodified sample, proving that surface modification effectively inhibits lattice oxygen precipitation and interface side reactions, and improves the electrochemical stability of the material.

[0023] Figure 5 :Comparison of half-cell cycle performance of O3 cathode materials at different rates before and after rare earth metal surface modification. The results show that the discharge capacity of the modified battery at each rate is better than that of the original sample, indicating that surface modification not only improves the cycle stability, but also significantly improves the rate performance of the material, providing the possibility for high-power applications. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0025] Embodiment 1:

[0026] O3-phase layered transition metal NaNi 0.33 Fe 0.33 Mn 0.33 O 2 For example, the raw material is prepared by solid phase sintering, and the target ion doped is one of alkali metal, alkaline earth metal, and rare earth element. If you buy a commercial product, you can directly proceed to step 2. The preparation includes the following steps:

[0027] S1: Preparation of NaNi by high temperature solid phase sintering 0.33 Fe 0.33 Mn 0.33 O 2 (NFM) Main material: NiO, Fe 2 O 3 、MnO 2 and Na 2 CO 3 Add high energy ball mill according to stoichiometric ratio, wherein Na 2 CO 3 The excess is 5 mol%; the ball mill speed is 1000-1800 r / min, and the ball milling time is 30-180 min. The mixed powder is pressed into tablets, sintered at 800-1000°C in a muffle furnace in an air atmosphere for 10-24 hours to obtain the NFM positive electrode material, which is immediately stored in an argon glove box.

[0028] S2: Prepare the ion exchange liquid phase environment with a non-protonic solvent (N-methylpyrrolidone solution), prepare the complexing agent polyvinyl pyrrolidone and the target ion (Lu 3+ ) nitrate solution.

[0029] S3: The sintered NFM particles are ground and sieved and added to the mixed solution, heated to 80°C and stirred vigorously for 4 hours, washed several times with pure aprotic solvent to remove residual ions, filtered and vacuum dried.

[0030] S4: Calcine at 400-1000°C for 0.5-10h to obtain the final material, and store it in an argon glove box.

[0031] Figure 1 and Figure 2 The scanning electron microscope image (SEM) and X-ray diffraction pattern (XRD) after surface metal ion modification show that the surface of the modified material is smooth and free of impurities, and the XRD crystallinity is good, which is consistent with the layered structure of the O3 phase and has no additional impurities. It can be concluded from the performance in Table 1 that Example 1 has the highest Coulomb efficiency and 100-cycle retention rate, proving that the reversibility of the electrochemical process is good. At the same time, the capacity of Example 1 is comparable to that of the original material, proving that surface ion modification does not affect the effective capacity, and improves the cycle stability while maintaining the energy density advantage of the O3-type positive electrode.

[0032] Embodiment 2:

[0033] In order to prove that different types of ions (alkali metals, alkaline earth metals, rare earth elements) can realize the present invention, this embodiment is different from Example 1 in that alkaline earth element ions are used for modification, calcium salts with equimolar concentrations are selected in step 2 to replace rare earth salts as target ions, and pure aprotic solvents are used, and the remaining steps are the same as Example 1. It can be seen from the performance in Table 1 that compared with Example 1, the 0.1C capacity is slightly improved, and the 100-cycle capacity retention rate is slightly reduced, but it is still significantly higher than that of Comparative Example 1, which can illustrate that the present invention has universal applicability in the selection of metal ions.

[0034] Embodiment 3:

[0035] In order to prove that different types of aprotic solvents can realize the present invention, the difference between this embodiment and embodiment 1 is that acetone is selected instead of N-methylpyrrolidone aprotic solvent in step 2, and the remaining steps are the same as those in embodiment 1. It can be seen from the performance in Table 1 that compared with the embodiment, the 0.1C capacity and the 100-cycle capacity retention rate are slightly reduced, but the cycle stability is still significantly higher than that of comparative example 1, which can illustrate the universality of the present invention in the selection of aprotic solvents.

[0036] Comparative Example 1:

[0037] In order to demonstrate the importance of ion exchange to the modification of O3 phase positive electrode materials, this comparative example does not carry out ion exchange, that is, transition metal oxides and sodium carbonate are added to a high-energy ball mill according to a stoichiometric ratio, wherein the sodium carbonate is in excess of 3 mol%; the ball mill is milled at 1700 r / min for 45 minutes. The mixed powder is pressed into tablets and calcined at 900°C for 15 hours in a muffle furnace air atmosphere to obtain the NFM positive electrode material, which is immediately stored in an argon glove box. It can be seen from the performance in Table 1 that comparative example 1 and example 1 have similar 0.1C capacities, but the 100-cycle cycle retention rates are quite different, at 69.1% and 90.4% respectively, and the coulombic efficiency also decreases by about 4%. It can be explained that the present invention has greatly improved the comprehensive performance while maintaining the capacity advantage of the raw materials.

[0038] Comparative Example 2:

[0039] In order to demonstrate the importance of ion exchange to construct a surface gradient symbiotic layered structure for the modification of O3 phase positive electrode materials, this comparative example adopts uniform doping of the target ion bulk phase and adds the target ions during the ball milling of the precursor. That is, in the ball milling of step 1 of Example 1, an additional 2% of the target ion oxide is added, mixed with the transition metal oxide and sodium carbonate and ball milled. The mixed powder is pressed into a tablet and calcined at 900°C for 15 hours in an air atmosphere. It can be seen from the performance in Table 1 that compared with Example 1, the coulomb efficiency is slightly reduced, the 100-cycle cycle retention rate is significantly reduced, and the 0.1C capacity is greatly reduced by 14%, and the initial capacity is reduced to 140.18 mAh g-1. Although this modification method has a higher cycle retention rate than that of Comparative Example 1, it sacrifices the capacity and reduces the energy density.

[0040] Performance Testing

[0041] The modified O3 positive electrode material obtained in the above examples and comparative examples was mixed with the conductive agent acetylene black and the binder (PVDF) in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added and stirred evenly to form a mixed slurry, which was coated on aluminum foil, vacuum dried at 120°C for 12 hours, and cut into positive electrode sheets for button-type half-cells. The button-type cells were assembled in a glove box. The half-cell counter electrode was sodium metal, the diaphragm was Whatman's glass fiber membrane, and the electrolyte concentration was 1 mol L -1 NaClO 4 The solvent was propylene carbonate (PC), and 5% fluoroethylene carbonate (FEC) was added. After the assembled button cell was left at room temperature for 12 h, the cell voltage ranged from 2 to 4.2 V and activated at a low current rate of 1C (1C = 130 mAh g -1 ) times for charge and discharge cycles, the performance test results of the positive electrode material are shown in Table 1 below:

[0042]

[0043] As can be seen from Table 1, the method for surface-doped layered battery positive electrode material provided by the present invention and the positive electrode material prepared therefrom, while maintaining the high specific capacity and high coulombic efficiency of the O3 material, significantly improves the cycle stability, ion mobility and rate performance, large current charge and discharge cycle capability and air stability.

[0044] Advantages and positive effects of the present invention

[0045] 1. Significantly improve cycle stability. Figure 4The half-cell 1C cycle performance was demonstrated. The half-cell cycle stability of the ion surface doped sample was significantly improved in the low current and 2-4.2V voltage range, with the 1C 200 cycle retention rate increased by about 37.2% (from 45.0% to 82.2%); the 2C 400 cycle retention rate increased by about 40% (from 33.6% to 73.4%).

[0046] 2. Improve ion mobility and rate performance. Figure 5 The results show that the capacity of the ion-doped samples is better than that of the original samples at different rates. The discharge capacities at 0.1, 0.2, 0.5, 1, 2, 5 and 10C rates are 165.5, 158.6, 150.9, 143.6, 134.1, 121.2 and 110.6 mAh g, respectively. –1 Especially at 10C rate, it can still maintain 110mAhg –1 The 10C capacity of the original material is less than 80 mAh g –1 .

[0047] 3. Improve the high current charge and discharge cycle capability. At 10C = 1300mAhg –1 Under current, the initial capacity of the ion surface modified sample reaches 120 mAh g –1 After 500 cycles, the capacity retention rate is 70.8%, while the capacity retention rate of the unmodified sample is 18.4%, an increase of 51%.

[0048] 4. Improved coulombic efficiency. As shown in Table 1, the O3-type bulk material provides excellent specific capacity. The ion surface modified sample provides a higher first-cycle coulombic efficiency (coulombic efficiency = discharge capacity / charge capacity) than the original material under the condition of equivalent capacity, thus improving the cycle reversibility.

[0049] 5. Improve air stability. O3-type sodium batteries are highly air-sensitive, but the electrochemical performance of the ion-surface-modified samples remains stable after exposure to air for 24 hours, with a capacity loss of 7.5%; under the same conditions, the original material loses 21.4% of its capacity.

[0050] From the perspective of chemical principles, the solvent-assisted I n+ Surface reconstruction, part I n+ Enter the surface of the positive electrode particles and build a uniform layer of Na 1-x I y Ni 0.33 Fe 0.33 Mn 0.33 O 2Gradient intergrowth layer. Through argon ion beam-assisted X-ray photoelectron spectroscopy at different depths, the concentration of I element decreases from the surface to the bulk phase, proving the formation of a gradient lattice co-doping structure. The addition of I enhances the interlayer force of the layered oxide, significantly improves the structural stability, and inhibits the irreversible reaction of lattice oxygen. At the same time, during the electrochemical charge and discharge of Na + During the embedding and disengaging process, I n+ It plays a supporting role between the layers, avoiding structural collapse under high sodium removal conditions and improving cycle stability. n+ , causing local lattice changes, improving ion mobility and rate performance. Due to the surface enrichment of I, the concentration of I in places that are easily exposed to air reduces the erosion of air on the O3-type sodium cathode, thereby further improving air stability.

[0051] In summary, the surface ion doping method is universal and improves the reversibility and comprehensive electrochemical performance of the overall positive electrode structure.

[0052] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A surface-doped layered battery positive electrode material, characterized in that: The general structural formula of the material is Na 1-x I y TMO2, wherein 0≤x<1, 0≤y<1, I is one or more of alkali metals, alkaline earth metals, rare earth metal elements such as Li, Ca, Sr, Ba, Zn, K, La~Lu, and TM is one or more of metal elements such as Ni, Co, Mn, Fe, Cu, Al, Mg, Cr, etc.

2. A method for preparing a surface-doped layered battery positive electrode material, characterized in that: The steps include: a) Using solid phase sintering, sol-gel, coprecipitation or commercial purchase to obtain layered sodium ion oxide Na with good crystallinity 1-x TMO2(x≥0); b) The positive electrode material Na 1-x TMO2 is placed in a metal salt (I n+ ) and an auxiliary complexing agent in a non-protonic solvent solution, and the target ions are made to participate in the reconstruction of the layered material surface by microwave, heating, stirring, and ultrasound; c) filtering, washing and annealing the mixture after the reaction.

3. The preparation method according to claim 2, characterized in that: The aprotic solvent in step b) is acetone, dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

4. The preparation method according to claim 2, characterized in that: The metal salts in step b) are sulfates, halides, nitrates, phosphates or complex salts that can be dissolved in organic solvents.

5. The preparation method according to claim 2, characterized in that: The doping ions in step b) are alkali metals, alkaline earth metals or rare earth elements.

6. The preparation method according to claim 2, characterized in that: The auxiliary complexing agent in step b) is a small molecule or a macromolecule of phytic acid, tannic acid, dopamine, or polyvinyl pyrrolidone.

7. The preparation method according to claim 2, characterized in that: The annealing temperature in step c) is in the range of 400-1000° C., the annealing time is 0.5-10 hours, and the annealing atmosphere is selected from air, argon or oxygen atmosphere.

8. The surface-modified sodium ion battery layered cathode material according to claim 1, characterized in that: The material has high first coulombic efficiency, excellent cycle performance and rate performance.

9. Use of the surface-doped layered battery positive electrode material according to claim 1 in sodium ion batteries.

Citation Information

Patent Citations

  • High-voltage positive electrode material capable of realizing structure reconstruction based on surface layer ion exchange reaction and preparation method of high-voltage positive electrode material

    CN113921786A

  • Multi-ion co-doped layered oxide sodium ion battery positive electrode material and preparation method thereof

    CN117913266A

  • T2 / O2 / O3 configuration lithium ion battery positive electrode material and rapid preparation method and application thereof

    CN118954626A

  • Ni-Fe-Mn-based layered oxide sodium ion positive electrode material as well as preparation method and application thereof

    CN118969977A

  • Positive electrode material and preparation method therefor, positive electrode plate, and sodium ion battery

    WO2023097984A1

Cited By

  • Aluminum-driven lattice-regulated high-performance layered sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN122102218A

  • Aluminum-driven lattice-regulated high-performance layered sodium-ion battery cathode material, and preparation method and application thereof

    CN122102218B